Integrative genomic and functional characterization of a feline milk–derived Lactiplantibacillus plantarum MNN reveals host-specific adaptation and ecological safety - Gong, Xinyu; Wang, Xue; Chen, Lu; Huang, Huiming; Wen, Min (Frontiers in Microbiology, 2026)
Feline milk serves as a natural reservoir of host-adapted microorganisms that shape early-life gut microbiota and immune development. Our previous work identified Pediococcus acidilactici M22 from feline milk, which showed robust gastrointestinal tolerance, antioxidant capacity, and safety, providing the first evidence that feline milk–derived probiotics could be suitable for simulated pet milk formulations. However, P. acidilactici species possess limited genomic versatility and metabolic adaptability, warranting exploration of other lactic acid bacteria with broader functional repertoires. MNN exhibited superior acid and bile tolerance (99.83% survival at pH 2.5 and 88% at 0.3% bile) compared with M22 (59.93 and 84.38%, respectively), indicating enhanced gastrointestinal resilience. It demonstrated notable antioxidant capacity (DPPH 52.64%, ABTS 55.59%, superoxide 63.17%) and increased serum SOD and GSH while reducing MDA in mice, reflecting a stronger antioxidative defense than M22, whose effects were primarily systemic. Genome sequencing revealed a 3.29 Mb chromosome—1.23 Mb larger than M22—harboring 3,091 coding sequences enriched in stress response (groEL, dnaK, trxA), antioxidant (katA, gshA), and antimicrobial (plnE, plnF) genes, as well as expanded membrane transport and carbohydrate metabolism pathways. Unlike M22, MNN also preserved gut microbial homeostasis in vivo, maintaining α/β diversity and subtly enriching beneficial genera (Oscillibacter, Adlercreutzia) without dysbiosis. Functional prediction confirmed stable carbohydrate and amino acid metabolism, with no enrichment of resistance or virulence genes. Compared with P. acidilactici M22, L. plantarum MNN exhibits higher genomic plasticity, stronger antioxidative capacity, and distinct ecological compatibility, marking a functional transition from “safety-verified probiotic” to “host-adapted microbiota-stabilizing probiotic.” Integrating genomic, functional, and ecological analyses, this study identifies MNN as a next-generation probiotic candidate for enhancing intestinal homeostasis and antioxidant defense in companion animals.